Developing affordable housing : a practical guide for nonprofit organizations - Hecht, Bennett L., 1959- (John Wiley and Sons, 1999)
Getting started. Projecting costs, income, and expenses. Raising capital. Enhancing feasibility and packaging the project. Purchasing and developing the property.